Outcome after discontinuing anticoagulant therapy in women with venous thromboembolism during hormonal use. Issue 151 (March 2017) - Blanco-Molina, Ángeles; Trujillo-Santos, Javier; Pesavento, Raffaele; Rosa, Vladimir; Falgá, Conxita; Tolosa, Carles; Mazzolai, Lucia; Sampériz, Ángel; Duce, Rita; Monreal, Manuel; ,
ABSTRACT: Introduction: Whether women developing venous thromboembolism (VTE) while using hormonal therapy should be classified as having "unprovoked" or "provoked" VTE is controversial. Methods: We used the RIETE (Registro Informatizado Enfermedad TromboEmbólica) database to compare the rate of symptomatic VTE recurrences after discontinuing anticoagulation in 3 subgroups of women aged ≤ 50 years without cancer, pregnancy or puerperium: (1) those with hormonal therapy and no additional risk factors (hormonal users only); (2) those with unprovoked VTE; and (3) those with additional risk factors, with or without hormonal therapy. Results: As of March 2016, 1513 women had been followed-up for at least one month after discontinuing anticoagulation. Of these, 654 (43%) were hormonal users only, 390 (26%) had unprovoked VTE and 469 (31%) had transient risk factors with or without hormonal therapy. After discontinuing anticoagulation, the rate of VTE recurrences in women with hormonal use only (2.44 per 100 patient-years; 95% CI: 1.53–3.69) was significantly lower than in those with unprovoked VTE (6.03; 95% CI: 3.97–8.77) and similar to those with transient risk factors (2.58; 95% CI: 1.50–4.13). Interestingly, the rate of VTE recurrences presenting as pulmonary embolism in women with hormonal use only (0.55 per 100 patient-years; 95% CI: 0.18–1.29) was similar to those with transient risk factors (0.46; 95% CI: 0.09–1.33) and 4-fold lower than in women with unprovoked VTE (2.23; 95% CI: 1.07–4.10). Conclusions: After discontinuing anticoagulation, the rate of VTE recurrences in hormonal users only was significantly lower than in women with unprovoked VTE and similar to the rate in women with additional risk factors.